MIKROFASIES DAN DIAGENESA BATUGAMPING FORMASI ZAAG DI PULAU MISOOL DAN SEKITARNYA - Mulyadi, Dedi (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2010)
The study of carbonate rocks of Zaag Formation shows that the carbonate rock of Paleo-cene-Eocene occurred in Misool Island and outcropped among the rock of Paleozoik– Tertiary. The field survey shows that the Zaag Formation is outcropped at the mid part of the Misool Island from the west to east and also at several the surrounding small islands. The petrography analysis indicated that there are two facies forming the Zaag Formation, indicated found it was form at shoal environment of Packstone Facies and Grainstone Facies. The diagenesis process observed at the thin section is micritisation, cementation, dissolution and tectonic activity.